(untitled) (Research, Society and Development, 2021)
Objective: To analyze the social representations of old age, aging and being old according to elderly men and women. Methodology: This is a qualitative research, using the Theory of Social Representations by Serge Moscovici, with elderly people living in a middle class neighborhood in the Metropolitan Region of Salvador – Bahia – Brazil. Data were collected through a semi-structured interview script, with open questions formulated by the researchers, which were recorded and transcribed in full and underwent thematic content analysis. Results: The 60 research participants – 30 men and 30 women – had an average of 73 years and 72 years, respectively. As for the investigated social representations, the following categories emerged: old age as natural life process, physical limitation/tiredness and subjective issue; aging as accepting finitude with limits and changes, having wisdom/experience and time to spend/live a lot; and being old as time of life having passed/having more limitations, having experience of life/wisdom and thinks they don’t have to learn or do anything else/lose optimism. Conclusion of the study: The social representations of the researched aged people are different regarding the main categories that we highlight, with contents related to social knowledge/practices linked to human development, limitations, the passage of time, wisdom and subjective issues. We understand from the results that being old is a challenge for the participants in view of the negative consequences pointed out, sometimes naturalized, sometimes presented as socially constructed and experienced in everyday life at this stage of human development, so much so that, generally, they don’t recognize themselves as old.